Kompas.com and The Jakarta Post Covid-19 news articles representation: A critical discourse analysis - Firdausi, Annisa Nurul; Sahayu, Wening (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
This paper used Critical Discourse Analysis to identify the ideology behind the news article in The Jakarta Post and Kompas.com by exposing the sort of ideology they hold. The pandemic which has become a part of our life since 2020 up until now inevitably change our representation as well. English and bahasa Indonesia-based is used to stress both the languages' representations. This paper employs Fairclough's Three-Dimensional Framework along with Halliday's Systemic Functional Grammar and Multimodality by Kress and Leeuwen to obtain further analysis. 20 news articles from each of the newspapers were selected with the total of 40 news articles for both of the newspaper on the Covid-19 related news for Critical Discourse Analysis. From the analysis, it is found that social, political, and cultural ideology existed in the news articles. Both of the newspaper tried to give people's awareness in the Covid-19 current condition by giving informative news articles.Keywords: three-dimensional framework, systemic functional grammar, multimodality